2019
DOI: 10.1001/jamaneurol.2018.2505
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cell-to-Cell Transmission of Pathological Tau

Abstract: IMPORTANCE Intracellular tau protein aggregates are a pathological hallmark of neurodegenerative tauopathies, including Alzheimer disease (AD), progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), and Pick disease. Emerging evidence supports a model of cell-to-cell transmission of proteinaceous pathological tau seeds, which leads to recruitment and templated fibrillization of endogenous cellular tau followed by the spread of abnormal tau throughout the brain. These findings lead to the strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
181
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(201 citation statements)
references
References 80 publications
17
181
0
3
Order By: Relevance
“…Our independently validated findings provide strong support for the notion that tau spreads across synaptic connections in an activity-dependent manner, as suggested by preclinical findings [14][15][16] . Our results may also motivate future studies to investigate tau spreading in other tauopathies such as primary age-related tauopathy, progressive nuclear palsy or corticobasal degeneration where tau pathology may spread via similar mechanisms [51][52][53] . Since tau is the strongest driver of cognitive decline in AD, potential interventions could target connectivity-related spreading mechanisms 16 or silencing of amyloid-induced neuronal hyperactivity that may promote tau spreading 54,55 .…”
Section: Discussionmentioning
confidence: 73%
“…Our independently validated findings provide strong support for the notion that tau spreads across synaptic connections in an activity-dependent manner, as suggested by preclinical findings [14][15][16] . Our results may also motivate future studies to investigate tau spreading in other tauopathies such as primary age-related tauopathy, progressive nuclear palsy or corticobasal degeneration where tau pathology may spread via similar mechanisms [51][52][53] . Since tau is the strongest driver of cognitive decline in AD, potential interventions could target connectivity-related spreading mechanisms 16 or silencing of amyloid-induced neuronal hyperactivity that may promote tau spreading 54,55 .…”
Section: Discussionmentioning
confidence: 73%
“…pS214Tau Traffics Between Neurons. Data from mouse models have demonstrated that phosphorylated tau can traffic within neural networks (83), for example from the ERC to "infect" hippocampal neurons (84). ImmunoEM has captured this process in the aging primate cortex, revealing pS214Tau trafficking between neurons in middle-aged ERC (7) and in aged dlPFC (40).…”
Section: Aging Rhesus Monkeys: Unique Opportunity To Study the Etiolomentioning
confidence: 99%
“…Many studies have shown that pathological tau aggregates can propagate from cell to cell through transmission of proteopathic tau seeds (Gibbons et al, 2019). Under this framework, our laboratory and others showed that different structural conformations of misfolded tau (tau strains) form in human tauopathy brains and underlie the heterogeneity of tauopathies (Clavaguera et al, 2013; Kaufman et al, 2016; Narasimhan et al, 2017; Sanders et al, 2014).…”
Section: Introductionmentioning
confidence: 99%